1997
DOI: 10.1016/s0005-2736(96)00241-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer mediated by cationic lipids: lack of a correlation between lipid mixing and transfection

Abstract: Complexes of DNA with cationic lipids are used to transfect eukaryotic cells. The mechanism of transfection is unknown, but it has been suggested that the complexes are taken up into the cell by endocytosis, after which fusion of the cationic lipids with the membranes of intracellular vesicles would allow the DNA to escape into the cytoplasm. Here, we have compared transfection of CHO-K1 cells with lipid mixing measured by fluorescence assays, using liposomes or complexes with plasmid DNA of the cationic lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 36 publications
5
44
0
Order By: Relevance
“…On the other hand, the highest transfection with APL-LPs were obtained in vitro with a slightly higher P/N between 1.5 and 2 (L9-LP: 1.69), whereas L9-LP with a P/N ratio of 3.2 was much more effective in vivo. This is consistent with the findings of several other groups [33][34][35][36][37][38] indicating that a slight positive charge (charge ratio between 1 and 2) supports the binding of the complex to the (negatively charged) cell membrane, whereas nucleic acid compaction rather than surface charge was critical for an efficient nuclear trafficking. 39 On the other hand, some reports describe other ratios for more efficient complexes, 10,38,[40][41][42] which indicated that the charge ratio is not the only factor responsible for the transfection efficacy.…”
Section: Alkylphospholipid Vesicle Mediated Gene Transfer R Zeisig Et Alsupporting
confidence: 92%
“…On the other hand, the highest transfection with APL-LPs were obtained in vitro with a slightly higher P/N between 1.5 and 2 (L9-LP: 1.69), whereas L9-LP with a P/N ratio of 3.2 was much more effective in vivo. This is consistent with the findings of several other groups [33][34][35][36][37][38] indicating that a slight positive charge (charge ratio between 1 and 2) supports the binding of the complex to the (negatively charged) cell membrane, whereas nucleic acid compaction rather than surface charge was critical for an efficient nuclear trafficking. 39 On the other hand, some reports describe other ratios for more efficient complexes, 10,38,[40][41][42] which indicated that the charge ratio is not the only factor responsible for the transfection efficacy.…”
Section: Alkylphospholipid Vesicle Mediated Gene Transfer R Zeisig Et Alsupporting
confidence: 92%
“…There have been studies which have linked the zeta potential to the transfection efficiency of cationic liposomes, 35 and others where no correlation has been found. 26 Although there may be a correlation, we do not believe that the zeta potential of the lipoplexes plays as great a role in lipofection as does the size of the lipoplex. Our measurements show that, while both the addition of polyanions and serum reduce the zeta potential of MLV lipoplexes at a 2:1 charge ratio to a similar extent, the transfection efficiency increases dramatically with polyanion-induced size increase, but the size and transfection efficiency remain low in the presence of polyanions plus serum (Figures 2a, 3a, 4a and 6a).…”
Section: Fluorescence Of Cells Which Have Been Exposed To Fluorescentmentioning
confidence: 88%
“…Previous findings have determined that either lipoplex size did not correlate with lipofection 26 or that lipoplexes 27 or liposome-polymer-DNA complexes 37 of smaller size are more efficient than larger sized complexes. In some of these reports, the sizes of complexes studied did not encompass the entire range of sizes necessary to elucidate any correlation.…”
Section: Fluorescence Of Cells Which Have Been Exposed To Fluorescentmentioning
confidence: 96%
See 1 more Smart Citation
“…In most cases, these lipids are mixed with an equimolar amount of a ''helper'' lipid. Most frequently, the neutral lipid DOPE is used, since this is known to enhance transfection efficiency (Felgner et al, 1994;Gao and Huang, 1995;Stegmann and Legendre, 1997;Zhou and Huang, 1994), due to its ability to facilitate the formation of cationic liposomes and to its tendency to form non-bilayer phases that may contribute to the destabilization of the endosomal membrane (Farhood et al, 1995;Felgner et al, 1994;Legendre and Szoka, 1992;Zhou and Huang, 1994). On the other hand, cholesterol (Chol) constitutes another promising ''helper'' lipid, since it has been demonstrated that high levels of transfection can be obtained both in vitro and in vivo, upon its association with a cationic lipid (Crook et al, 1998;Templeton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%